Sex differences in pre-surgical respiratory physiotherapy impact on hospital and ICU stay in cardiac surgery patients: An observational study - Jorge Montero-Cámara; Francisco José Ferrer-Sargues; David Cuesta Peredo; Adrián Sarria Cabello; María José Segrera Rovira; Juan Antonio Margarit Calabuig; Noemí Valtueña-Gimeno; Juan Pardo; María Luz Sánchez-Sánchez (PLoS ONE, 2025)
Introduction Cardiovascular diseases may be amenable to surgical intervention. To mitigate post-surgical complications, diverse strategies are employed, including pre-habilitation programs. This study examines the effect of an unsupervised pre-surgical respiratory physiotherapy program on both sexes in terms of hospital and intensive care unit (ICU) stay lengths, as well as the incidence of post-surgical complications, their severity, and mortality risk. Methodology Retrospective observational study of 418 adults who underwent open-heart surgery between 2018 and 2022. The subjects were divided into two sex-based groups based on attendance at individual pre-surgical physiotherapy sessions. A Mann-Whitney U test was employed to evaluate the impact of the pre-surgical respiratory physiotherapy program and a Kruskal-Wallis rank-sum test to assess its influence on both sexes. Additionally, a multiple linear regression analysis was conducted to evaluate the impact of various variables on overall length of stay. Results The mean age of women was higher (p = 0.002), and they exhibited longer mean lengths of ICU (p = 0.004) and hospital stays (p = 0.031). In both sexes, a statistically significant reduction in LOS was observed among those undergoing a respiratory physiotherapy program. The linear regression analysis indicated that male sex was associated with a reduction in hospital and ICU stay lengths (p < 0.001). Although women experienced a higher number of complications (p = 0.043), no differences in severity levels or mortality risk were observed between sexes. Conclusion An unsupervised home pre-surgical physiotherapy program based on ventilatory exercises can reduce hospital and ICU stay for both men and women. Notwithstanding the higher incidence of complications in women, no differences in severity or mortality risk were observed between sexes.